Identification of Risk Loci for Radiotoxicity in Prostate Cancer by Comprehensive Genotyping of TGFB1 and TGFBR1 - Manuel Guhlich (MDPI AG, 2021)
Genetic variability in transforming growth factor beta pathway (TGFB) was suggested to affect adverse events of radiotherapy. We investigated comprehensive variability in TGFB1 (gene coding for TGFβ1 ligand) and TGFBR1 (TGFβ receptor-1) in relation to radiotoxicity. Prostate cancer patients treated with primary radiotherapy (n = 240) were surveyed for acute and late toxicity. Germline polymorphisms (n = 40) selected to cover the common genetic variability in TGFB1 and TGFBR1 were analyzed in peripheral blood cells. Human lymphoblastoid cell lines (LCLs) were used to evaluate a possible impact of TGFB1 and TGFBR1 genetic polymorphisms to DNA repair capacity following single irradiation with 3 Gy. Upon adjustment for multiplicity testing, rs10512263 in TGFBR1 showed a statistically significant association with acute radiation toxicity. Carriers of the Cytosine (C)-variant allele (n = 35) featured a risk ratio of 2.17 (95%-CI 1.41–3.31) for acute toxicity ≥ °2 compared to Thymine/Thymine (TT)-wild type individuals (n = 205). Reduced DNA repair capacity in the presence of the C-allele of rs10512263 might be a mechanistic explanation as demonstrated in LCLs following irradiation. The risk for late radiotoxicity was increased by carrying at least two risk genotypes at three polymorphic sites, including Leu10Pro in TGFB1. Via comprehensive genotyping of TGFB1 and TGFBR1, promising biomarkers for radiotoxicity in prostate cancer were identified.